Ni-doped MoS2 modified graphitic carbon nitride layered hetero-nanostructures as highly efficient photocatalysts for environmental remediation - Koutsouroubi, Eirini D.; Vamvasakis, Ioannis; Minotaki, Maria G.; Papadas, Ioannis T.; Drivas, Charalampos; Choulis, Stelios A.; Kopidakis, Georgios; Kennou, Stella; Armatas, Gerasimos S. (My University, 2021)
Highly efficient and cost-effective photocatalysts are among the most prominent targets in the field of environmental remediation and clean energy production. Here, we report that 2D/2D layer heterostructures composed of exfoliated Ni-doped MoS2 nanosheets and g-C3N4 layers can carry out photocatalytic Cr(VI) reduction in aqueous solutions with outstanding activity, exhibiting apparent QYs as high as 29.6 % and 23.7 % at 375 and 410 nm. We show that Ni doping of MoS2 markedly increases the photochemical activity, which, together with electrochemical, spectroscopic and theoretical DFT studies, arises from the enhanced carrier density and mobility at the Ni-MoS2/g-C3N4 interface. In addition to the favorable charge transport properties, delineation of the photoinduced oxidation reactions by gas monitoring techniques reveals that the high efficiency also arises from fast water oxidation kinetics. The results of this work mark an important step forward in understanding and designing low-cost and earth-abundant catalysts for detoxification of Cr(VI)-contaminated industrial effluents.
Keywords: Cr(VI) reduction; Carbon nitride; MoS2; Photocatalysis; Oxygen evolution